Quasi-Fiscal Deficits and Energy Conditionality in Selected CIS Countries - Saavalainen, Tapio (IMF Working Papers; Working Paper ;, 2006)
Quasi-fiscal deficits of public utility companies are common in all member countries of the Commonwealth of Independent States (CIS). They constitute a significant impediment to efficient resource allocation and endanger macroeconomic stability. This paper presents a simple framework for measuring and monitoring such deficits and highlights their macroeconomic relevance. It reviews the progress under IMF conditionality aimed at correcting these imbalances during 1993-2003. The paper suggests that the extensive conditionality under the IMF-supported programs has yielded only limited progress in reducing the energy sector's financial imbalances. In conclusion, different policy options are discussed in light of the lessons learned.